1985
DOI: 10.1161/01.cir.72.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of diltiazem and atenolol on exercise-induced regional myocardial ischemia in conscious dogs.

Abstract: The effect of combination therapy with diltiazem and atenolol on the regional myocardial blood flow-function relationship was studied in eight conscious dogs with chronic coronary artery stenosis. An ameroid constrictor and hydraulic occluder were placed around the left circumflex coronary artery, sonomicrometers were implanted for measuring wall thickness in control and ischemic regions, and regional myocardial blood flow was measured with the microsphere method. Eighteen days (average) after surgery, resting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(6 citation statements)
references
References 43 publications
1
4
0
1
Order By: Relevance
“…Bush and coworkers [19] found that in dogs with temporary occlusion of the LAD, propranolol and diltiazem significantly decreased the extent of histological necrosis, as well as the macrohistochemically determined infarct. Results similar to these have also been presented by Matsuzaki et al [20]. In some studies, beta-blocking agents have also been shown to inhibit the reflex tachycardia occurring in some patients given calcium-channel antagonists.…”
Section: Ischemic Myocardial Syndromessupporting
confidence: 81%
“…Bush and coworkers [19] found that in dogs with temporary occlusion of the LAD, propranolol and diltiazem significantly decreased the extent of histological necrosis, as well as the macrohistochemically determined infarct. Results similar to these have also been presented by Matsuzaki et al [20]. In some studies, beta-blocking agents have also been shown to inhibit the reflex tachycardia occurring in some patients given calcium-channel antagonists.…”
Section: Ischemic Myocardial Syndromessupporting
confidence: 81%
“…Nevertheless, when normalizing blood flow to a single cardiac cycle and thus considering heart rate, the relationships at two different heart rates are superimposable (Figure 7) ( Indolfi et al , 1989 ). In a series of studies, all pharmacological agents that attenuate exercise‐induced myocardial ischaemia (β‐blockers, calcium antagonists, nitrates and their combinations) were demonstrated to operate along such consistent flow–function relationship, further strengthening the concept of perfusion–contraction matching ( Matsuzaki et al , 1984a , 1984b , 1985 ; Guth et al , 1986 ).…”
Section: Heart Rate and The Pathophysiology Of Coronary Blood Flowmentioning
confidence: 90%
“…However, when the heart rate reduction caused by beta-adrenoceptor blockade with atenolol was prevented by atrial pacing, regional myocardial blood flow of the ischemic area was even reduced compared to the untreated situation. In recent experiments in conscious dogs, combined administration of atenolol and diltiazem increased regional blood flow and function during exercise-induced poststenotic myocardial ischemia to a greater extent than administration of either drug alone [77] (Figure 8). The aggravation of myocardial ischemia was possibly due to an unmasking of alpha-adrenergic constriction in the ischemic coronary microcirculation.…”
Section: Attenuation Of Beta-adrenoceptor-mediated Myocardial Blood Fmentioning
confidence: 92%